Spatial Assessment of Groundwater Potential Zones of East New Britain province, Papua New Guinea - Hejumacla Oboko, Sujoy Kumar Jana, Tingneyuc Sekac (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Technological advancement nowadays is very helpful with cost effective and time consuming techniques by incorporating GIS and Remote Sensing techniques to delineate groundwater potential map with wide-ranging tools used for the assessment of water resources, its management and conservation. This project is to outline the zonation of groundwater and produces a potential Groundwater map of East New Britain Province. The techniques used are Multi-Influencing Factor (MIF) and Analytical Hierarchy Process (AHP) for the evaluation and assignment of ranks and weights on the different factors such as Lithology, Geomorphology, Soil, Slope, LU/LC, Rainfall, Lineaments & Drainage Density and Vegetation. After assigning each factors with its weightages and ranking individual factors depending on their influence on groundwater potential areas, it is then overlay in the GIS environment using Weighted Sum technique. From the overall results, the groundwater potential areas in the study area are classified into five (5) categories ranging from very good, good, moderate, poor and very poor. With these categories; Very Good (21.90%), Good (37.60%), Moderate (25.81%), Poor (12.39%) and Very Poor (2.30%) which the representation is explicitly decipher that most of the area is potentially suitable for groundwater occurrence. Concurring, Pomio and Gazelle districts have spatially shows moderate to Very Good potential areas of groundwater compared to Rabaul and Kokopo districts having low potential areas of groundwater. After integrating all these 9 thematic layers with their assigned weights, it clearly indicates potential groundwater areas which can decipher potential groundwater sources for drinking water supply, recharge locations and planning for water security.